Conceptualizing the origin of life in terms of evolution. (13th November 2017) - Takeuchi, N.; Hogeweg, P.; Kaneko, K.
Abstract : In this opinion piece, we discuss how to place evolution in the context of origin-of-life research. Our discussion starts with a popular definition: 'life is a self-sustained chemical system capable of undergoing Darwinian evolution'. According to this definition, the origin of life is the same as the origin of evolution: evolution is the 'end' of the origin of life. This perspective, however, has a limitation, in that the ability of evolution in and of itself is insufficient to explain the origin of life as we know it, as indicated by Spiegelman's and Lincoln and Joyce's experiments. This limitation provokes a crucial question: What conditions are required for replicating systems to evolve into life? From this perspective, the origin of life includes the emergence of life through evolution: evolution is a 'means' of the origin of life. After reviewing Eigen's pioneering work on this question, we mention our ongoing work suggesting that a key condition might be conflicting multi-level evolution. Taken together, there are thus two questions regarding the origin of life: how evolution gets started, and how evolution produces life. Evolution is, therefore, at the centre of the origin of life, where the two lines of enquiry must meet. This article is part of the themed issue 'Reconceptualizing the origins of life'.